Building Sustainable Minds: The Role of ESD Integration in Ninth-Grade on Environmental Issues - Sihombing, Rizky Agassy; Muslim, Muslim; Rahman, Taufik; Anwar, Sjaeful (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2024)
Education for Sustainable Development (ESD) is an integral part of achieving the three pillars of human development: social development, economic growth, and environmental preservation. ESD is a global initiative that encompasses broader issues than those addressed solely by the Indonesian Government a collective responsibility to foster ESD as a fundamental value for current and future generations. This study employed a descriptive research method, using a sustainability awareness questionnaire adapted from Hassan et al. The study aimed to comprehensively assess sustainability awareness among 53 ninth-grade students at SMPN 17 Medan. The primary objective was to outline and categorize the profile of sustainability awareness, focusing on emotional, behavioral, and practical dimensions, while also examining gender differences. Data were systematically analyzed using a Likert scale and validated instruments, aligned with sustainability awareness indicators. The results indicated a high level of sustainability awareness, with emotional awarenessat 89.6%, followed by behavioral and attitude awareness at 82.1%. However, practical awareness was at 66.4%, indicating a potential area for improvement. Female students demonstrated higher awareness (85.7%) compared to male students (73.0%). These findings highlight the need for targeted educational interventions to enhance practical sustainability awareness and ensure equitable participation among all students.